Nano modified epoxy building thermal insulation material and preparation method thereof
Through nanomodified epoxy resin materials, combined with graphene aerogel and other nanomaterials, the problems of insufficient insulation performance, poor mechanical properties, poor waterproof performance and single functions of traditional building insulation materials are solved, and the multifunctional performance is improved, which is suitable for the insulation and energy-saving needs of modern buildings.
Patent Information
- Application Number
- CN202510307538.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-11
AI Technical Summary
Existing building insulation materials have problems such as insufficient insulation performance, poor mechanical properties, poor waterproof performance and single functions, which are difficult to meet the diversified needs of modern buildings for material performance.
Nanomodified epoxy building insulation materials are used to form a material with multifunctional properties by combining nanomaterials such as graphene aerogel, nanosilver particles, nanosilica, hollow glass microbeads, paraffin microcapsules and other nanomaterials with epoxy resin.
It significantly improves the compressive strength, thermal conductivity, dry apparent density and waterproof performance of the material, meets the multifunctional needs of insulation, mechanics, antibacterial and temperature regulation, and is suitable for high-end buildings in thermal insulation and energy-saving buildings.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building thermal insulation materials, and more specifically, to a nano-modified epoxy building thermal insulation material and a preparation method thereof. Background Art
[0002] With the continuous improvement of building energy-saving requirements, the research and application of building insulation materials are becoming more and more extensive. Although traditional building insulation materials, such as polystyrene boards, rock wool and polyurethane foam, have met the insulation needs to a certain extent, they still have the following problems: Insufficient insulation performance: Traditional materials have a high thermal conductivity and are difficult to meet the requirements of ultra-low energy consumption buildings. Poor mechanical properties: Traditional materials have low compressive strength and are prone to deformation or damage, affecting the durability of the building structure. Poor waterproof performance: Traditional materials have a high volume water absorption rate and are prone to water absorption and failure in a humid environment. Single function: Traditional materials usually only have insulation functions and lack multifunctionality such as antibacterial and temperature regulation, making it difficult to meet the diverse requirements of modern buildings for material performance. Poor environmental protection: Some traditional materials release harmful substances during production and use, causing pollution to the environment.
[0003] In response to the above problems, there are some improvement schemes in the existing technology, for example: using nanomaterials (such as nano-silicon dioxide, nano-alumina) to modify thermal insulation materials to improve their mechanical properties and thermal insulation properties. However, the improvement scheme still has the following shortcomings: Poor dispersibility: Nanomaterials are easy to agglomerate in the matrix, affecting the uniformity and performance of the material. Single function: Existing materials are usually only improved for a certain performance, and it is difficult to meet the multi-functional requirements of thermal insulation, mechanics, antibacterial and temperature regulation at the same time. Complex process: The preparation process of existing materials is complex and it is difficult to achieve industrial production.
[0004] In summary, solving the problems existing in the prior art, such as insufficient thermal insulation performance, poor mechanical properties, poor waterproof performance and single function, has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] In order to overcome a series of defects in the prior art, the purpose of the present application is to provide a nano-modified epoxy building insulation material in view of the above-mentioned problems, which is composed of the following raw materials: 100 parts by weight of bisphenol A epoxy resin, 5-15 parts by weight of epoxy resin toughening agent, 0.5-2 parts by weight of antioxidant, 5-15 parts by weight of graphene aerogel, 1-3 parts by weight of nano-silver particles, 5-15 parts by weight of nano-silicon dioxide, 15-25 parts by weight of hollow glass microspheres, 5-15 parts by weight of paraffin microcapsules, and 30-50 parts by weight of epoxy resin curing agent.
[0006] Furthermore, the epoxy resin toughening agent is a rubber elastomer; the antioxidant is a hindered phenol; the particle size of the nano silver particles is 30-50nm; the particle size of the nano silicon dioxide is 20-40nm; and the particle size of the paraffin microcapsule is 1-5um.
[0007] Furthermore, the raw material also includes 1-3 parts by weight of a dispersant, and the dispersant is polyvinyl pyrrolidone.
[0008] Furthermore, the raw materials also include 1-3 parts by weight of a silane coupling agent, specifically KH-550.
[0009] Furthermore, the raw materials also include 2-6 parts by weight of glass fiber, the glass fiber is chopped glass fiber, and 5-15 parts by weight of flame retardant, and the flame retardant is aluminum hydroxide.
[0010] According to a second aspect of the present application, a method for preparing a nano-modified epoxy building thermal insulation material is provided, comprising the following steps.
[0011] Step 1: pre-treating graphene aerogel; surface modifying nano-silver particles; and pre-treating nano-silicon dioxide.
[0012] Step 2: Resin premixing: place 100 parts by weight of bisphenol A epoxy resin in a reaction kettle; heat to 60-70°C to reduce viscosity; add 5-15 parts by weight of epoxy resin toughener; high-speed shear mixing for 30-50 minutes; add 0.5-2 parts by weight of antioxidant and continue stirring for 15-30 minutes.
[0013] Step 3: Adding nanomaterials; slowly adding the pretreated graphene aerogel dispersion into the premixed bisphenol A epoxy resin; shearing and dispersing for 40-60 minutes using a high shear dispersing device; adding the pretreated nano silver particles in batches under stirring, and slowly adding the pretreated nano silicon dioxide under stirring; continuing high-speed shear stirring for 30-40 minutes.
[0014] Step 4: Adding auxiliary fillers: pre-mix the hollow glass microspheres with a small amount of bisphenol A epoxy resin; slowly add to the reactor and stir at a low speed; add paraffin microcapsules and stir gently for 15 minutes.
[0015] Step 5 Vacuum degassing: Place the mixture in a vacuum degassing device; degas for 20-30 minutes at a vacuum degree of 0.09-0.095 MPa; observe until no obvious bubbles are generated.
[0016] Step 6: Add curing agent: lower the mixture temperature to 40-45°C; slowly add 30-50 parts by weight of epoxy resin curing agent; stir at low speed for 5-10 minutes to avoid generating new bubbles.
[0017] Step 7: Molding and curing: pour the mixture into a pre-treated mold; pre-cure at room temperature for 2-4 hours; cure at 80-90°C for 4-6 hours; post-cure at 120-130°C for 2-4 hours; and cool naturally to room temperature.
[0018] Furthermore, in step 1, the graphene aerogel is pretreated by taking an appropriate amount of deionized water and adding a dispersant; adding the graphene aerogel to the dispersion; using a high-power ultrasonic processing device for ultrasonic dispersion treatment for 45-60 minutes; using an intermittent mode for ultrasonic treatment to avoid overheating; and maintaining the dispersion at a low temperature of 10-15°C to improve the dispersion effect.
[0019] Furthermore, in step 1, the surface of the nanosilver particles is modified by placing the nanosilver particles in an ethanol solution; adding a silane coupling agent KH-550; stirring at 50-60° C. for 20-50 minutes to perform surface modification; filtering and drying at 60° C. for 3-6 hours; and grinding into fine powder after drying for later use.
[0020] Furthermore, in step 1, the nano-silica is pretreated by placing the nano-silica in ethanol; adding a small amount of silane coupling agent KH-550; stirring at room temperature for 30-40 minutes; and drying at 60-70° C. until there is no free solvent.
[0021] Furthermore, step 4 may also include: adding chopped glass fibers and gently stirring until uniformly dispersed; adding flame retardants in batches, each time with an interval of 5-10 minutes; stirring until uniformly dispersed.
[0022] Compared with the prior art, the present application has the following beneficial effects.
[0023] This application optimizes the composition of nano-modified epoxy building insulation materials and adopts efficient preparation processes such as ultrasonic assistance, and exhibits excellent performance in compressive strength, thermal conductivity, dry apparent density and volume water absorption. It is suitable for applications in high-end building insulation, energy-saving buildings and special environments. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application, but the description of these embodiments should not be construed as limiting the scope of protection of the present application.
[0025] 1. Raw material selection.
[0026] Bisphenol A epoxy resin: The bisphenol A epoxy resin matrix used in this application can be selected from E-51. The dosage is 100 parts by weight. This matrix material has low cost and stable performance.
[0027] Epoxy resin toughening agent: specifically selected as rubber elastomer, the amount used is 5-15 parts by weight, preferably 10 parts by weight, to improve the impact resistance of the material.
[0028] Antioxidant: The antioxidant is a hindered phenol, 0.5-2 parts by weight, preferably 1.25 parts by weight, to improve the antioxidant properties of the material.
[0029] Graphene aerogel: Its usage is 5-15 parts by weight, preferably 10 parts by weight, which provides ultra-low thermal conductivity and high strength, improves thermal insulation and mechanical properties. The porous three-dimensional network structure of graphene aerogel provides extremely low thermal conductivity, making the material have excellent thermal insulation effect, which can effectively reduce building energy consumption.
[0030] Nanosilver particles: particle size is 30-50 nanometers. The dosage is 1-3 parts by weight, preferably 2 parts by weight. It provides antibacterial properties and inhibits the growth of microorganisms. The combination of graphene aerogel and nanosilver creates a synergistic enhancement effect of thermal, mechanical and biological properties. One material solves multiple problems at the same time.
[0031] The particle size of nano silicon dioxide is 20-40 nanometers, and the specific surface area is 30-60m² / g. The dosage is 5-15 parts by weight, preferably 10 parts by weight. Nano silicon dioxide enhances mechanical properties and thermal insulation properties, and surface modification improves dispersibility.
[0032] Hollow glass microspheres: The usage is 15-25 parts by weight, preferably 20 parts by weight. They are lightweight and have low thermal conductivity. They can replace part of aerogel to reduce costs.
[0033] Paraffin microcapsules: the dosage is 5-15 parts by weight, preferably 10 parts by weight, purchased from Shanghai Joule Wax Co., Ltd.
[0034] Epoxy resin curing agent: polyetheramine is used in an amount of 30-50 parts by weight, preferably 45 parts by weight, to ensure that the curing reaction is fully carried out and to improve the durability of the material.
[0035] Dispersant: specifically polyvinyl pyrrolidone, used in an amount of 1-3 parts by weight, preferably 2 parts by weight, to improve the dispersibility of the nanomaterial and prevent agglomeration.
[0036] Silane coupling agent: specifically selected from silane, KH-550, the amount of which is 1-3 parts by weight, preferably 2 parts by weight, to improve the interface bonding force between the nanomaterial and the fiber and the matrix.
[0037] Glass fiber, the glass fiber is short-cut glass fiber, and its usage is 2-6 parts by weight, preferably 4 parts by weight, to enhance mechanical properties.
[0038] Flame retardant: specifically aluminum hydroxide, with an amount of 5-15 parts by weight, preferably 10 parts by weight, to improve flame retardancy, and be environmentally friendly and non-toxic.
[0039] 2. Formula of nano-modified epoxy building insulation material.
[0040] 100 parts by weight of bisphenol A epoxy resin, 5-15 parts by weight of epoxy resin toughening agent, 0.5-2 parts by weight of antioxidant, 5-15 parts by weight of graphene aerogel, 1-3 parts by weight of nano silver particles, 5-15 parts by weight of nano silicon dioxide, 15-25 parts by weight of hollow glass micro beads, 5-15 parts by weight of paraffin microcapsules, and 30-50 parts by weight of epoxy resin curing agent; the epoxy resin toughening agent is a rubber elastomer; the antioxidant is a hindered phenol; the nano silver The particle size of the particles is 30-50nm; the particle size of the nano-silicon dioxide is 20-40nm; the particle size of the paraffin microcapsule is 1-5um; the raw materials also include 1-3 parts by weight of a dispersant, which is polyvinyl pyrrolidone; the raw materials also include 1-3 parts by weight of a silane coupling agent, which can be specifically KH-550; the raw materials also include 2-6 parts by weight of glass fiber, which is chopped glass fiber, and 5-15 parts by weight of a flame retardant, which is aluminum hydroxide.
[0041] 3. Preparation method of nano-modified epoxy building insulation material.
[0042] Phase 1: Nanomaterial pretreatment.
[0043] 1. Graphene aerogel pretreatment: Take an appropriate amount of deionized water and add 1-3 parts of dispersant (polyvinyl pyrrolidone); add 5-15 parts of graphene aerogel to the dispersion; use high-power ultrasonic processing equipment (power 500-800W) for ultrasonic dispersion treatment for 45-60 minutes; use intermittent mode (work 30 seconds, stop 10 seconds) for ultrasonic treatment to avoid overheating; keep the dispersion at a low temperature of 10-15°C to improve the dispersion effect.
[0044] 2. Surface modification of nanosilver particles: place 1-3 parts of nanosilver particles in an ethanol solution; add silane coupling agent KH-550 (10% of the total amount); stir at 50-60°C for 20-50 minutes to modify the surface; filter and dry at 60°C for 3-6 hours; grind into fine powder after drying for later use.
[0045] 3. Pretreatment of nano-silica: Place 5-15 parts of nano-silica in ethanol; add a small amount of silane coupling agent KH-550; stir at room temperature for 30-40 minutes; dry at 60-70°C until there is no free solvent.
[0046] Phase 2: Preparation of matrix resin system.
[0047] 4. Resin premixing: Place 100 parts of bisphenol A epoxy resin (E-51) in a reaction kettle; heat to 60-70°C to reduce viscosity; add 5-15 parts of epoxy resin toughening agent (rubber elastomer); high-speed shear mixing for 30-50 minutes (speed 1500-2000rpm); add 0.5-2 parts of antioxidant (hindered phenols) and continue stirring for 15-30 minutes.
[0048] The third stage: nano-functional material composite.
[0049] 5. Addition of nanomaterials: Slowly add the pretreated graphene aerogel dispersion to the premixed bisphenol A epoxy resin; use high shear dispersion equipment (shear rate> 5000s -1 ) shear dispersion for 40-60 minutes; add the pretreated nano silver particles in batches under stirring; slowly add the pretreated nano silicon dioxide under stirring; continue high-speed shear stirring for 30-40 minutes.
[0050] 6. Addition of auxiliary fillers: pre-mix 15-25 parts of hollow glass microspheres with a small amount of bisphenol A epoxy resin; slowly add to the reactor and stir at a low speed (to avoid breaking the microspheres); add 5-15 parts of paraffin microcapsules and stir gently for 15 minutes; finally add chopped glass fibers and stir gently until evenly dispersed; add 5-15 parts by weight of flame retardant in batches, with an interval of 5-10 minutes each time; stir until evenly dispersed.
[0051] The fourth stage: degassing and curing.
[0052] 7. Vacuum degassing: Place the mixture in a vacuum degassing device; degas for 20-30 minutes at a vacuum degree of 0.09-0.095 MPa; observe until no obvious bubbles are generated.
[0053] 8. Add curing agent: Lower the mixture temperature to 40-45°C; slowly add 30-50 parts of epoxy resin curing agent (polyetheramine); stir at low speed for 5-10 minutes to avoid generating new bubbles.
[0054] 9. Molding and curing: Pour the mixture into a pre-treated (coated with release agent and preheated to 40°C) mold; pre-cure at room temperature for 2-4 hours; cure at 80-90°C for 4-6 hours; post-cure at 120-130°C for 2-4 hours; cool naturally to room temperature.
[0055] Stage 5: Post-processing.
[0056] 10. Demolding and curing: After demoulding, cure under standard conditions (23±2°C, relative humidity 50±5%) for 7 days.
[0057] 4. Embodiment
[0058] Example 1: Preparation method and its ratio: 1. Pretreatment of graphene aerogel: Take an appropriate amount of deionized water, add 1 part of dispersant (polyvinyl pyrrolidone); add 5 parts of graphene aerogel to the dispersion; use high-power ultrasonic processing equipment (power 500W) for ultrasonic dispersion treatment for 45 minutes; ultrasonic treatment adopts intermittent mode (work for 30 seconds, stop for 10 seconds) to avoid overheating; the dispersion is kept in a low temperature environment of 10°C to improve the dispersion effect.
[0059] 2. Surface modification of nanosilver particles: place 1 part of nanosilver particles in an ethanol solution; add silane coupling agent KH-550 (10% of the total amount); stir at 50°C for 20 minutes to perform surface modification; filter and dry at 60°C for 3 hours; grind into fine powder after drying for later use.
[0060] 3. Pretreatment of nano-silica: Place 5 parts of nano-silica in ethanol; add a small amount of silane coupling agent KH-550; stir at room temperature for 30 minutes; and dry at 60°C until there is no free solvent.
[0061] Phase 2: Preparation of matrix resin system.
[0062] 4. Resin premixing: Place 100 parts of bisphenol A epoxy resin (E-51) in a reaction kettle; heat to 60°C to reduce viscosity; add 5 parts of epoxy resin toughener (rubber elastomer); high-speed shear mixing for 30 minutes (speed 1500rpm); add 0.5 parts of antioxidant (hindered phenols) and continue stirring for 15 minutes.
[0063] The third stage: nano-functional material composite.
[0064] 5. Addition of nanomaterials: Slowly add the pretreated graphene aerogel dispersion to the premixed bisphenol A epoxy resin; use high shear dispersion equipment (shear rate> 5000s -1 ) shear dispersion for 40 minutes; add the pretreated nano-silver particles in batches under stirring; slowly add the pretreated nano-silicon dioxide under stirring; continue high-speed shear stirring for 30 minutes.
[0065] 6. Addition of auxiliary fillers: pre-mix 15 parts of hollow glass microspheres with a small amount of bisphenol A epoxy resin; slowly add to the reactor and stir at a low speed (to avoid breaking the microspheres); add 5 parts of paraffin microcapsules and stir gently for 15 minutes; finally add chopped glass fibers and stir gently until evenly dispersed; add 5 parts by weight of flame retardant in batches, with an interval of 5 minutes each time; stir until evenly dispersed.
[0066] The fourth stage: degassing and curing.
[0067] 7. Vacuum degassing: Place the mixture in a vacuum degassing device; degas for 20 minutes at a vacuum degree of 0.09 MPa; observe until no obvious bubbles are generated.
[0068] 8. Add curing agent: Lower the mixture temperature to 40°C; slowly add 30 parts of epoxy resin curing agent (polyetheramine); stir at low speed for 5 minutes to avoid generating new bubbles.
[0069] 9. Molding and curing: Pour the mixture into a pre-treated (coated with release agent and preheated to 40°C) mold; pre-cure at room temperature for 2 hours; cure at 80°C for 4 hours; post-cure at 120°C for 2 hours; and cool naturally to room temperature.
[0070] Stage 5: Post-processing.
[0071] 10. Demolding and curing: After demoulding, cure under standard conditions (23±2°C, relative humidity 50±5%) for 7 days.
[0072] Example 2: Preparation method and its ratio: Phase 1: Pretreatment of nanomaterials.
[0073] 1. Graphene aerogel pretreatment: Take an appropriate amount of deionized water and add 3 parts of dispersant (polyvinyl pyrrolidone); add 15 parts of graphene aerogel to the dispersion; use high-power ultrasonic processing equipment (power 800W) for ultrasonic dispersion treatment for 60 minutes; ultrasonic treatment adopts intermittent mode (work 30 seconds, stop 10 seconds) to avoid overheating; the dispersion is kept at a low temperature environment of 15°C to improve the dispersion effect.
[0074] 2. Surface modification of nanosilver particles: place 3 parts of nanosilver particles in an ethanol solution; add silane coupling agent KH-550 (10% of the total amount); stir at 60°C for 50 minutes to perform surface modification; filter and dry at 60°C for 6 hours; grind into fine powder after drying for later use.
[0075] 3. Pretreatment of nano-silica: Place 15 parts of nano-silica in ethanol; add a small amount of silane coupling agent KH-550; stir at room temperature for 40 minutes; and dry at 70°C until there is no free solvent.
[0076] Phase 2: Preparation of matrix resin system.
[0077] 4. Resin premixing: Place 100 parts of bisphenol A epoxy resin (E-51) in a reaction kettle; heat to 70°C to reduce viscosity; add 15 parts of epoxy resin toughening agent (rubber elastomer); high-speed shear mixing for 50 minutes (speed 2000rpm); add 2 parts of antioxidant (hindered phenols) and continue stirring for 30 minutes.
[0078] The third stage: nano-functional material composite.
[0079] 5. Addition of nanomaterials: Slowly add the pretreated graphene aerogel dispersion to the premixed bisphenol A epoxy resin; use high shear dispersion equipment (shear rate> 5000s -1 ) shear dispersion for 60 minutes; add the pretreated nano-silver particles in batches under stirring; slowly add the pretreated nano-silicon dioxide under stirring; continue high-speed shear stirring for 40 minutes.
[0080] 6. Addition of auxiliary fillers: pre-mix 25 parts of hollow glass microspheres with a small amount of bisphenol A epoxy resin; slowly add to the reactor and stir at a low speed (to avoid breaking the microspheres); add 15 parts of paraffin microcapsules and stir gently for 15 minutes; finally add chopped glass fibers and stir gently until evenly dispersed; add 15 parts by weight of flame retardant in batches, with an interval of 10 minutes each time; stir until evenly dispersed.
[0081] The fourth stage: degassing and curing.
[0082] 7. Vacuum degassing: Place the mixture in a vacuum degassing device; degas for 30 minutes at a vacuum degree of 0.095 MPa; observe until no obvious bubbles are generated.
[0083] 8. Add curing agent: Lower the mixture temperature to 45°C; slowly add 50 parts of epoxy resin curing agent (polyetheramine); stir at low speed for 10 minutes to avoid generating new bubbles.
[0084] 9. Molding and curing: Pour the mixture into a pre-treated (coated with release agent and preheated to 40°C) mold; pre-cure at room temperature for 4 hours; cure at 90°C for 6 hours; post-cure at 130°C for 4 hours; and cool naturally to room temperature.
[0085] Stage 5: Post-processing.
[0086] 10. Demolding and curing: After demoulding, cure under standard conditions (23±2°C, relative humidity 50±5%) for 7 days.
[0087] Example 3: Preparation method and its ratio: Phase 1: Pretreatment of nanomaterials.
[0088] 1. Graphene aerogel pretreatment: Take an appropriate amount of deionized water and add 2 parts of dispersant (polyvinyl pyrrolidone); add 10 parts of graphene aerogel to the dispersion; use high-power ultrasonic processing equipment (power 650W) for ultrasonic dispersion treatment for 50 minutes; use intermittent mode (work for 30 seconds and stop for 10 seconds) to avoid overheating; keep the dispersion at a low temperature of 12.5°C to improve the dispersion effect.
[0089] 2. Surface modification of nanosilver particles: Place 2 parts of nanosilver particles in an ethanol solution; add silane coupling agent KH-550 (10% of the total amount); stir at 55°C for 30 minutes to perform surface modification; filter and dry at 60°C for 4 hours; grind into fine powder after drying for later use.
[0090] 3. Pretreatment of nano-silica: Place 10 parts of nano-silica in ethanol; add a small amount of silane coupling agent KH-550; stir at room temperature for 35 minutes; and dry at 65°C until there is no free solvent.
[0091] Phase 2: Preparation of matrix resin system.
[0092] 4. Resin premixing: Place 100 parts of bisphenol A epoxy resin (E-51) in a reactor; heat to 65°C to reduce viscosity; add 10 parts of epoxy resin toughener (rubber elastomer); high-speed shear mixing for 40 minutes (speed 1750rpm); add 1.25 parts of antioxidant (hindered phenols) and continue stirring for 22.5 minutes.
[0093] The third stage: nano-functional material composite.
[0094] 5. Addition of nanomaterials: Slowly add the pretreated graphene aerogel dispersion to the premixed bisphenol A epoxy resin; use high shear dispersion equipment (shear rate> 5000s -1 ) shear dispersion for 50 minutes; add the pretreated nano-silver particles in batches under stirring; slowly add the pretreated nano-silicon dioxide under stirring; continue high-speed shear stirring for 35 minutes.
[0095] 6. Addition of auxiliary fillers: pre-mix 20 parts of hollow glass microspheres with a small amount of bisphenol A epoxy resin; slowly add to the reactor and stir at a low speed (to avoid breaking the microspheres); add 10 parts of paraffin microcapsules and stir gently for 15 minutes; finally add chopped glass fibers and stir gently until evenly dispersed; add 10 parts by weight of flame retardant in batches, with an interval of 7.5 minutes each time; stir until evenly dispersed.
[0096] The fourth stage: degassing and curing.
[0097] 7. Vacuum degassing: Place the mixture in a vacuum degassing device; degas for 25 minutes at a vacuum degree of 0.0925 MPa; observe until no obvious bubbles are generated.
[0098] 8. Add curing agent: Lower the mixture temperature to 42.5°C; slowly add 40 parts of epoxy resin curing agent (polyetheramine); stir at low speed for 7.5 minutes to avoid generating new bubbles.
[0099] 9. Molding and curing: Pour the mixture into a pre-treated (coated with release agent and preheated to 40°C) mold; pre-cure at room temperature for 3 hours; cure at 85°C for 5 hours; post-cure at 125°C for 3 hours; and cool naturally to room temperature.
[0100] Stage 5: Post-processing.
[0101] 10. Demolding and curing: After demoulding, cure under standard conditions (23±2°C, relative humidity 50±5%) for 7 days.
[0102] Comparative Example: Samples were prepared according to the existing patent publication number: CN119430815A.
[0103] 5. Performance testing
[0104] 1. Thermal insulation performance test: The prepared nano-modified epoxy building insulation material is made into a sample and tested in accordance with the standard method of GB / T10294-2008 "Determination of steady-state thermal resistance and related properties of insulation materials - Guarded hot plate method". The thermal conductivity of the material is calculated by measuring the temperature gradient under steady-state heat flow.
[0105] The test results are as follows: Example 1: thermal conductivity can be controlled at 0.026 W / (m·K); Example 2: thermal conductivity can be controlled at 0.028 W / (m·K); Example 3: thermal conductivity can be controlled at 0.023 W / (m·K); Comparative example: thermal conductivity can be controlled at 0.06 W / (m·K). The present application is much lower than traditional thermal insulation materials and has excellent thermal insulation performance.
[0106] 2. Compressive strength test.
[0107] The test results are as follows: Example 1: compressive strength 16.9 MPa; Example 2: compressive strength 15.3 MPa; Example 3: compressive strength 18.6 MPa; Comparative example: compressive strength 4.8 MPa; This application is superior to traditional thermal insulation materials and is suitable for building structures with higher requirements on mechanical properties.
[0108] 3. Dry apparent density test.
[0109] The test results are as follows: Example 1: dry apparent density 365 kg / m³; Example 2: dry apparent density 315 kg / m³; Example 3 dry apparent density 225 kg / m³; Comparative example: dry apparent density 1506 kg / m³; This application reduces building load and is suitable for high-rise buildings and energy-saving buildings.
[0110] 4. Volume water absorption.
[0111] The test results are as follows: Example 1: volume water absorption rate ≤1.8%; Example 2: volume water absorption rate ≤1.7%; Example 3 volume water absorption rate ≤1.5%; Comparative example: volume water absorption rate ≤6%; This application is suitable for humid environments.
[0112] Based on all the test data, the thermal conductivity of the thermal insulation performance of this application is low: the thermal conductivity is ≤0.025 W / (m·K), which is much lower than that of traditional thermal insulation materials, significantly improving the thermal insulation effect. Significant energy-saving effect: the low thermal conductivity enables the material to effectively reduce building energy consumption and meet the requirements of ultra-low energy consumption buildings and green buildings. High compressive strength: the compressive strength is ≥15 MPa, which can withstand large loads and is suitable for building structures with high mechanical properties. Low dry apparent density: the dry apparent density is 200-400 kg / m³, which is a lightweight material that can significantly reduce the building load and is suitable for high-rise buildings and large-span structures. Convenient construction: the lightweight characteristics make the material easy to transport and install, reducing the difficulty and cost of construction; excellent waterproof performance: low volume water absorption: the volume water absorption is ≤2%, which is much lower than that of traditional thermal insulation materials (such as the volume water absorption of rock wool can reach more than 10%), and it can still maintain stable performance in a humid environment. Moisture-proof and mildew-proof: the low water absorption makes the material suitable for humid environments (such as basements, bathrooms, etc.), extending the service life.
[0113] The above embodiments are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A nano-modified epoxy building thermal insulation material, characterized in that: It is composed of the following raw materials: 100 parts by weight of bisphenol A epoxy resin, 5-15 parts by weight of epoxy resin toughening agent, 0.5-2 parts by weight of antioxidant, 5-15 parts by weight of graphene aerogel, 1-3 parts by weight of nano silver particles, 5-15 parts by weight of nano silicon dioxide, 15-25 parts by weight of hollow glass micro beads, 5-15 parts by weight of paraffin microcapsules, and 30-50 parts by weight of epoxy resin curing agent.
2. The nano-modified epoxy building thermal insulation material according to claim 1, characterized in that: The epoxy resin toughening agent is a rubber elastomer; the antioxidant is a hindered phenol; the particle size of the nano silver particles is 30-50nm; the particle size of the nano silicon dioxide is 20-40nm; and the particle size of the paraffin microcapsule is 1-5um.
3. The nano-modified epoxy building thermal insulation material according to claim 1, characterized in that: The raw materials also include 1-3 parts by weight of a dispersant, and the dispersant is polyvinyl pyrrolidone.
4. The nano-modified epoxy building thermal insulation material according to claim 1, characterized in that: The raw materials also include 1-3 parts by weight of a silane coupling agent, and the silane coupling agent is KH-550.
5. The nano-modified epoxy building thermal insulation material according to claim 1, characterized in that: The raw materials also include 2-6 parts by weight of glass fiber, which is chopped glass fiber, and 5-15 parts by weight of flame retardant, which is aluminum hydroxide.
6. A method for preparing a nano-modified epoxy building thermal insulation material, used for preparing the nano-modified epoxy building thermal insulation material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: pretreating the graphene aerogel: taking an appropriate amount of deionized water and adding a dispersant; adding the graphene aerogel to the dispersion; and performing ultrasonic dispersion treatment using a high-power ultrasonic treatment device; Surface modification of nano-silver particles: placing nano-silver particles in an ethanol solution; adding silane coupling agent KH-550 and stirring; Pre-treat the nano-silica: place the nano-silica in ethanol; add a small amount of silane coupling agent KH-550 and stir; Step 2: Resin premixing: place bisphenol A epoxy resin in a reaction kettle; heat to 60-70°C to reduce viscosity; add epoxy resin toughening agent; high-speed shear mixing for 30-50 minutes; add antioxidant and continue stirring for 15-30 minutes; Step 3: adding nanomaterials; slowly adding the pretreated graphene aerogel dispersion to the premixed bisphenol A epoxy resin; using a high shear dispersion device for shear dispersion for 40-60 minutes; Add the pretreated nano-silver particles in batches under stirring, and slowly add the pretreated nano-silicon dioxide under stirring; continue high-speed shear stirring for 30-40 minutes; Step 4: Adding auxiliary fillers: pre-mix the hollow glass microspheres with a small amount of bisphenol A epoxy resin; slowly add to the reaction kettle and stir at a low speed; add paraffin microcapsules and stir gently for 15 minutes; Step 5 Vacuum degassing: Place the mixture in a vacuum degassing device; degas for 20-30 minutes at a vacuum degree of 0.09-0.095 MPa; observe until no obvious bubbles are generated; Step 6 Curing agent addition: Lower the mixture temperature to 40-45°C; slowly add the epoxy resin curing agent; stir at low speed for 5-10 minutes to avoid generating new bubbles; Step 7: Molding and curing: pour the mixture into a pre-treated mold; pre-cure at room temperature for 2-4 hours; cure at 80-90°C for 4-6 hours; post-cure at 120-130°C for 2-4 hours; and cool naturally to room temperature.
7. The method for preparing a nano-modified epoxy building thermal insulation material according to claim 6, characterized in that: In step 1, during the pretreatment of graphene aerogel: ultrasonic dispersion treatment for 45-60 minutes; ultrasonic treatment is performed in an intermittent mode to avoid overheating; the dispersion is maintained at a low temperature of 10-15°C to improve the dispersion effect.
8. The method for preparing a nano-modified epoxy building thermal insulation material according to claim 6, characterized in that: In step 1, in the surface modification of the nanosilver particles: the stirring temperature is 50-60° C., the stirring time is 20-50 minutes, and the surface modification is performed; the particles are filtered and dried at 60° C. for 3-6 hours; and the particles are ground into fine powder for later use after drying.
9. The method for preparing a nano-modified epoxy building thermal insulation material according to claim 6, characterized in that: In step 1, during the pretreatment of nano-silicon dioxide: the stirring temperature is room temperature, the stirring time is 30-40 minutes; and the mixture is dried at 60-70°C until there is no free solvent.
10. The method for preparing a nano-modified epoxy building thermal insulation material according to claim 6, characterized in that: Step 4 also includes: adding chopped glass fibers and gently stirring until uniformly dispersed; adding flame retardants in batches, each time with an interval of 5-10 minutes; stirring until uniformly dispersed.
Citation Information
Patent Citations
Inorganic micro / nanoparticle / polymer composite building thermal-insulation aerogel material and preparation method thereof
CN103113043A
Method for preparing graphene aerogel and application thereof
CN106082202A
Graphene / nano-silica / epoxy resin composite material and preparation method thereof
CN107459774A
Energy-saving thermal insulation material and preparation method thereof
CN108793932A
High thermal conductivity epoxy resin composite material as well as preparation method and application thereof
CN109535659A
Cited By
Epoxy resin composite antioxidant adhesive and preparation method thereof
CN120329898A